Signaling pathways of oxidative stress response: the potential therapeutic targets in gastric cancer - Liu, Yingying; Shi, Yu; Han, Ruiqin; Liu, Chaoge; Qin, Xiaogang; Li, Pengfei; Gu, Renjun (Frontiers in Immunology, 2023)
Gastric cancer is one of the top causes of cancer-related deaths globally. Although novel treatment strategies have been developed, attempts to eradicate gastric cancer have been proven insufficient. Oxidative stress arising from is continually present in the human body. Increasing evidences show that contributes significantly to the development of gastric cancer, either initiation, promotion and progression cancer cells or causing cell death. As a result, the purpose of this article is to review the role of oxidative stress response and the subsequent signaling pathways as well as potential oxidative stress-related therapeutic targets in gastric cancer. Understanding the pathophysiology of gastric cancer and developing new therapies for gastric cancer depend on more research focusing on the potential contributors to oxidative stress and gastric carcinogenesis.